2014
DOI: 10.7731/kifse.2014.28.6.001
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Air Egress Velocity in Vestibule Pressurization System : Damper Locationfor Uniform Air Egress Velocity in the case of Two Fire Doors

Abstract: Vestibule pressurization system should produce uniform air egress velocity to prevent the intrusion of smoke into escape route when fire accidents occur inside a building and fire doors are open for evacuation of people. Air supplying units in the vestibule need to be arranged by taking account of the location of doors and the volume of the vestibule. In this study, computational fluid dynamics (CFD) simulations were conducted for the vestibule where two doors are installed varying the location of a damper and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…방화문에서 평균 방연풍속을 확보하더라도 국부적으로 역류가 발생할 수 있고 이를 최소화하기 위하여 댐퍼의 급 기 방향에 따라 방화문에서의 방연풍속을 확인할 필요가 있다 (6,9) . Figure 7은 화재가 없을 때 급기 방향을 달리하여 방화문의 높이에 따라 방화문에서 10 s 동안의 평균 방연 풍속을 나타낸 것이다.…”
Section: 댐퍼의 급기 방향에 따른 방화문에서의 방연풍속unclassified
“…방화문에서 평균 방연풍속을 확보하더라도 국부적으로 역류가 발생할 수 있고 이를 최소화하기 위하여 댐퍼의 급 기 방향에 따라 방화문에서의 방연풍속을 확인할 필요가 있다 (6,9) . Figure 7은 화재가 없을 때 급기 방향을 달리하여 방화문의 높이에 따라 방화문에서 10 s 동안의 평균 방연 풍속을 나타낸 것이다.…”
Section: 댐퍼의 급기 방향에 따른 방화문에서의 방연풍속unclassified
“…They found that in the case upward 45 gradient of supply damper's blade, the simulation results that air flow of upper vestibule is steady but back-flow phenomenon occurred at the bottom. Seo and Shin [11,12] investigated the characteristics of air flow in the vestibule with multiple fire doors in an apartment building and the damper location for uniform air egress velocity in the case of two fire doors by using the method of CFD numerical simulation. Their research found that when the damper in the vestibule is located at the center of the wall opposite to two fire doors, the uniform air egress velocity can be obtained.…”
Section: Introductionmentioning
confidence: 99%